Household Management of Childhood Diarrhoea: A Population-based Study in Nicaragua - Becker-Dreps, Sylvia (International Centre for Diarrhoeal Disease Research, Bangladesh, 2014)
Diarrhoea remains an important cause of mortality and morbidity among children in Nicaragua. As the majority of diarrhoeal cases are treated at home and appropriate household management can lessen severity of diarrhoea, the objective of this study was to examine household management of childhood diarrhoea. A simple random sample of households was selected from the Health and Demographic Surveillance Site-León. Parents or caretakers of children below five years of age, who developed diarrhoea (n=232), were surveyed about household diarrhoea management practices in 2011. Fifty-seven percent of children received oral rehydration therapy (ORT) in the home prior to visiting any health facility. We encountered certain practices in contradiction with WHO recommendations for the management of diarrhoea in communities: 41% of children were offered protein-rich foods less frequently during diarrhoeal episodes, 20% of children were nursed less frequently or not at all during diarrhoeal episodes, and zinc supplementation was recommended at only 39% of visits with healthcare providers. Our findings provide insights for efforts to improve the household management of childhood diarrhoea in Nicaragua.